Is the number of siblings associated with dietary patterns in adolescents? The 1993 birth cohort of Pelotas (Brazil). - F O Meller; M C F Assunção; A A Schäfer; C Loret de Mola; D L Dahly; J S Vaz; F C Barros (PLoS ONE)
Our study aimed to estimate the association between number of siblings and dietary patterns in adolescents. Prospective longitudinal study was developed using data from the birth cohort of the city of Pelotas, Brazil, which included 5249 participants. At the 18-year-old follow-up, from 4563 individuals located, 4106 were interviewed (follow-up rate 81.3%). Of these, 3751 were included in our principal component analysis of dietary patterns. Regular dietary intake of 45 food groups over the previous year was measured with a food frequency questionnaire. We identified four patterns, which accounted for 40% of the total variance in food group consumption. These were labeled "Protein and fast food", "Fruit and vegetables", "Common Brazilian", and "Sweets, soft drinks, and dairy products". Crude and adjusted analyses of the association between number of siblings and dietary patterns were performed using linear regression. The number of siblings was positively associated with a higher adherence to each dietary pattern, with the exception of the "Common Brazilian" patterns, for which there was no apparent relationship with number of siblings. The findings showed that a greater number of siblings is related to a more diverse diet in the later adolescence, which may predict better nutrient adequacy and health outcomes.